INCIDENCE OF PSYCHOTROPIC DRUGS PRESCRIBED IN CHILDREN AND ADOLESCENTS WITH AUTISM AT EL. TEGANI-ALMAHI REFERENCE HOSPITAL KHARTOUM SUDAN. A CROSS-SECTIONAL STUDY. - Shogar, Alrazi Eisa; Shayoup, Mohammed Elhassan; Umar, Mohammed Sani (Student's Journal of Health Research Africa, 2024)
Background: Autism spectrum disorder (ASD) among vulnerable populations frequently presents with complex mental health diagnoses, and psychotropic medications are often a component of comprehensive biopsychosocial treatment plans for these conditions. The primary aim of this study is to determine the incidence of usage of psychotropic drugs and to assess the response of psychotropic medications prescribed in children and adolescents with autism in a resource-constrained setting in Khartoum Sudan. Materials and methods: Following an institutional review board approval, Department of Innovation, Development and Scientific Research, Ministry of Health, Khartoum State (IDSREC-2020-EATA/44/A), A cross-sectional retrospective hospital-based study was conducted from January 2018 to Jan-2021 among 261 children and adolescents aged 1 to 17 years diagnosed with ASD using The Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition, Text Revision (DSM-5-TR) as a guideline. SPSS version 25. Results: The prevalence of ASD was greater in males than females; 45% of autistic patients have at least one comorbid disease. Attention Deficit Hyperactivity Disorder (ADHD), learning disability (LD), and epilepsy are the three most comorbid diseases among autistic patients. The Average number of psychotropic drugs per prescription was 1.8 out of 2.61. The most often prescribed medications among this group were risperidone (49%), methylphenidate (33%), and valproic acid (15%). All the patients received at least one psychotropic prescription; 30% of the patients were receiving polytherapy. Non-adherence of the patient to their medication account for 24%. This indicated the efficacy of other treatment approaches and the importance of combining medication and non-medication therapy. Conclusion: The study revealed a significant use of psychotropic medication, with a notable emphasis on antipsychotics. There is a high incidence of prescription rates for psychotropic medications for comorbid psychiatric disorders.